2005
DOI: 10.1088/0953-8984/17/14/011
|View full text |Cite
|
Sign up to set email alerts
|

Saffman–Taylor instability in yield stress fluids

Abstract: Pushing a fluid with a less viscous one gives rise to the well known Saffman-Taylor instability. This instability is important in a wide variety of applications involving strongly non-Newtonian fluids that often exhibit a yield stress.Here we investigate the Saffmann-Taylor instability in this type of fluid, in longitudinal flows in Hele-Shaw cells. In particular, we study Darcy's law for yield stress fluids. The dispersion equation for the flow is similar to the equations obtained for ordinary viscous fluids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 16 publications
7
26
1
Order By: Relevance
“…This led to detailed instability criteria and descriptions and analysis of various trends (Coussot 1999, Fontana et al 2013, Ebrahimi et al 2016. The validation of these conclusions by confrontation with experimental data remains extremely limited, and when this was done a reasonable agreement for the finger size (Lindner et al 2000, Derks et al 2003, Maleki-Jirsaraei et al 2005, but a strong discrepancy was found concerning the instability criterion (Barral et al 2010), suggesting some important effect is missed.…”
Section: Saffman-taylor Instabilitymentioning
confidence: 99%
“…This led to detailed instability criteria and descriptions and analysis of various trends (Coussot 1999, Fontana et al 2013, Ebrahimi et al 2016. The validation of these conclusions by confrontation with experimental data remains extremely limited, and when this was done a reasonable agreement for the finger size (Lindner et al 2000, Derks et al 2003, Maleki-Jirsaraei et al 2005, but a strong discrepancy was found concerning the instability criterion (Barral et al 2010), suggesting some important effect is missed.…”
Section: Saffman-taylor Instabilitymentioning
confidence: 99%
“…where r ¼ ½r 2 0 þ _ Vt=ðπbÞ 0.5 is the time-dependent average radius of the interface, Γ e the interfacial tension between the two fluids, _ γ I ¼ 3 _ Vð2πr 0 b 2 Þ −1 the shear rate at the injection hole, and η 2 ð_ γ r Þ the shear rate-dependent viscosity [18,52,53], with _ γ r ¼ ð4r 0 _ γ I =rÞ the shear rate calculated at a distance r from the injecting hole, where the onset of the instability is observed. The shear-rate-dependent viscosity η 2 is measured independently by standard rheometry [54].…”
Section: B Analysis Of the Viscous Fingering Patternsmentioning
confidence: 99%
“…For ease of analysis, most studies carried out in the past on ST instability of non-Newtonian fluids have focused on the Hele-Shaw cell for modeling homogenous porous media. And, virtually all aspects of non-Newtonian behavior have been addressed in these studies (see, for example, [12][13][14][15] for shear-thinning fluids, [16] for elastic fluids, [17][18][19] for thixotropic fluids, and [20][21][22] for viscoplastic fluids). Having said this, it should be conceded that, due to the complexity of the viscous fingering phenomenon and the diversity of the parameters involved, most studies carried out in the past have been concerned with a linear stability analysis only (see, for example, [20]).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the effect of yield stress on the nonlinear growth of fingers still remains unexplored in the theoretical domain. Such nonlinearities (which exhibit themselves by tip-splitting and/or side-branching) have been witnessed in experimental studies by Lindner et al [21], Maleki-Jirsaraei et al [22], and Van Damme et al [23]. A theoretical prediction of such nonlinear effects has not been carried out in the past, perhaps because of its inherent difficulty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation